A Case of Anaplastic Large Cell Lymphoma Misdiagnosed with Keloid - Kong D; Deng D (Dove Medical Press, 2023)
Di Kong, Danqi Deng Department of Dermatology, Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, 650101, People's Republic of ChinaCorrespondence: Danqi Deng, Fax +86-871-65351214, Email danqid128@sina.comAbstract: We report a case of a patient initially diagnosed with keloid and eventually diagnosed by skin histopathology and immunohistochemistry with primary cutaneous ALK-negative anaplastic large cell lymphoma.Keywords: primary cutaneous ALK-negative anaplastic large cell lymphoma, keloid, misdiagnosis